Factors Affecting the Cardiologists' Prescribing Attitudes in Dubai and the Northern Emirates: A Cross-sectional Study - Jeroudy, Heba; Al-Tabakha, Moawia; Ashames, Akram; Jairoun, Ammar Abdulrahman (Libyan International Medical University Journal, 2023)
Background The growing concern of irrational drug use that leads to adverse events requires attention to investigate the prescription patterns. For cardiovascular drugs, this could increase patients' risk of developing a heart attack or stroke and coronary artery disease. This study particularly examines cardiologist behaviors that influence prescription patterns. The influence of pharmaceutical companies' promotions and other factors affecting their prescriptions in the United Arab Emirates (UAE), mainly in Dubai and the Northern Emirates private hospitals and clinics, were investigated.Methods Online survey questions were undertaken using the structured questionnaire, and the determined sample size of the cardiologists working in Dubai and the Northern Emirates was 59 using randomly generated numbers from the available cardiologists' registry and assuming 95% confident with the 80% response rate. Ratings of the prescribing behavior were done using the original Bloom's cutoff points, which were updated and adjusted to evaluate UAE cardiologists' general prescribing practices.Results The average prescribing behavior score was moderate (76.5%; 95% confidence interval [CI], 75.1–77.8). Better prescribing patterns were observed among the cardiologists from Dubai compared with the Northern Emirates (odds ratio 4.24; 95% CI, 1.06–16.97). Continued medical education sponsored by pharmaceutical companies was the main influential factor (96.6%) affecting the cardiologists in changing their prescription. A total of 40.7% of the cardiologists believed in changing the prescription from brand to generic, while 43% stated that clinical updates, including evidence from new studies, were among the other factors affecting their prescribing behavior pattern.Conclusion The cardiologists' prescribing behaviors in Dubai and the Northern Emirates are above average and the cardiologists are aware of the unethical acceptance of pricey gifts. Cardiologists in Dubai and the Northern Emirates are considered ethical in adopting a new medication in agreement with similar studies conducted regionally, as their primary motivation is the welfare of patients, which will help them rationally select medication.
Keywords: cardiologists; prescription pattern; attitude; pharmaceutical companies; clinical updates